Transnational Marriages of Rohingya Refugees: Legal Challenges of Islamic Family Law in Malaysia - Rodziana Mohamed Razali; Aizat Khairi; Tasneem Rahmatullah (Electronicpublications.org Ltd, 2024)
Indexed by Scopus